2015
DOI: 10.3390/en8088814
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Measuring the Heat Collection Rate and Heat Loss Coefficient of Water-in-Glass Evacuated Tube Solar Water Heaters Based on Artificial Neural Networks and Support Vector Machine

Abstract: Abstract:The determinations of heat collection rate and heat loss coefficient are crucial for the evaluation of in service water-in-glass evacuated tube solar water heaters. However, the direct determination requires complex detection devices and a series of standard experiments, which also wastes too much time and manpower. To address this problem, we propose machine learning models including artificial neural networks (ANNs) and support vector machines (SVM) to predict the heat collection rate and heat loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Therefore, finding a method to predict the compressed liquid density directly is a good way to estimate the numerical values without tedious experiments. To provide a convenient methodology for predictions, a comparative study among different possible models is necessary [26,27,34,35]. Here, we used the Song and Mason equation, SVM, and ANNs to develop theoretical and machine learning models, respectively, for predicting the compressed liquid densities of R227ea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, finding a method to predict the compressed liquid density directly is a good way to estimate the numerical values without tedious experiments. To provide a convenient methodology for predictions, a comparative study among different possible models is necessary [26,27,34,35]. Here, we used the Song and Mason equation, SVM, and ANNs to develop theoretical and machine learning models, respectively, for predicting the compressed liquid densities of R227ea.…”
Section: Discussionmentioning
confidence: 99%
“…The plane helps improve the predictive ability of the model and reduce the error which occurs occasionally when predicting and classifying. Figure 1 shows the main structure of a SVM [34,35]. The letter "K" represents kernels [36].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…ANNs were developed by NeuralTools ® software (trial version, Palisade Corporation, Ithaca, NY, USA) [22,23]. A general regression neural network (GRNN) [24,25] and multilayer feed-forward neural networks (MLFNs) [26,27] were used from the software. The SVM model was developed by Matlab software (Libsvm package [21]).…”
Section: Model Developmentmentioning
confidence: 99%
“…As its name implies, machine learning is able to "learn" the highly complicated relationships between the independent and dependent variables via non-linear "black box" data processing. During the past decades, it has been widely used in many scientific and industrial areas, such as biology [7][8][9], medicine [10][11][12], energy [13][14][15][16][17][18][19], environment [20][21][22], engineering [23][24][25], and information technology (IT) [26,27]. These application studies indicate that machine learning techniques have dramatically boosted the development of many different areas.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the deep neural network (DNN) has raised broad interests due to its strong learning capacity and the popular concept of deep learning techniques [32,33]. Previous studies have shown that different neural network algorithms have different advantages for practical applications [17,18,34,35].…”
Section: Introductionmentioning
confidence: 99%